A Very Short, Fairly Interesting and Reasonably Cheap Book about Management - Cunliffe, Ann L (SAGE Publications, Ltd. (UK), 2021)
Conceived by Chris Grey, SAGE’s ′A Very Short, Fairly Interesting and Reasonably Cheap’ series shies away from the sterility of conventional textbooks, offering students an informal and accessible overview of the field which challenges the traditional literature. A bestseller from the series, this new edition of A Very Short, Fairly Interesting and Reasonably Cheap Book about Management by internationally renowned academic Ann L. Cunliffe has been updated to reflect current research. With inclusion of more international examples and coverage of ethical management, new ways of working and recent successes and failures in leadership in relation to the Covid pandemic, this book will stretch, surprise and reward business and management students at undergraduate, postgraduate and MBA levels.